New City: New City - Phanuvichayo, Phramaha Phanuvich; Purisuttamo, Pharmaha Maghavin; Pamoottor, Phrakhrusangharak Yodsawi (RATANABUTH JOURNAL, 2024)
This academic article aims to find patterns in the development of new city construction. The construction of city approaches focuses on creating holistic spaces. There is careful planning. It creates a city that is sustainable and able to support growth efficiently. Format and planning are important steps. It define the purpose of the new city. It includes setting attainable goals for the city, such as land development. It has a transport network and organized parks. It chose the location of the new city to be naturally and environmentally suitable. It includes factors such as access to natural resources. It provides access to important infrastructure such as roads, sewers, electrical systems, and water systems to enable the city to function efficiently. It creates amenities for the population, such as schools, hospitals, parks, shops, and entertainment venues. It enhances the quality of life for the population. It reorganizes cities so that they are efficient. It includes appropriate development policies such as land management, traffic management, and environmental management. New cities are built through complex and time-consuming processes. It involves collaboration between the public and private sectors for the best results. It is the long-term development of a new city. Building new cities is important, affecting the long-term sustainable development of communities and countries. It considers sustainability by using natural resources. It is also important to reduce the environmental impact of this process.